Molecular epidemiology and antimicrobial resistance profiles of Salmonella isolates from dairy heifer calves and adult lactating cows in a Mediterranean pasture-based system of Australia - J.W. Aleri; S. Sahibzada; A. Harb; A.D. Fisher; F.K. Waichigo; T. Lee; I.D. Robertson; S. Abraham (Journal of Dairy Science, 2022)
ABSTRACT: Dairy cows can be reservoirs of foodborne pathogens such as Salmonella that pose serious public health risks to humans. The study was designed to examine the molecular epidemiology and antimicrobial resistance profiles of Salmonella isolates from dairy heifer calves and adult lactating cows in the pasture-based system of Australia. A total of 838 animals (328 heifer calves and 510 lactating cows) from 22 farms were sampled. Overall, 54 Salmonella isolates were recovered (calves 28/328 and cows 26/510). A herd-level Salmonella prevalence of 50% (95% confidence interval: 31%–69%) was recorded. Within-herd prevalence for Salmonella ranged between 4%–29% and 4%–45% among the heifer calves and adult lactating cows, respectively. Three different serovars were identified with Salmonella Infantis being the most common serovar (n = 33, 61%) followed by Salmonella Kiambu (n = 20, 37.0%) and one isolate of Salmonella Cerro (2%). The highest antimicrobial resistance prevalence of Salmonella isolates was found against streptomycin (n = 31, 57%), followed by cefoxitin (n = 12, 22%), ceftriaxone (n = 2, 4%), and chloramphenicol (n = 1, 2%). Multiple class resistance was observed on 4 isolates against cefoxitin, chloramphenicol, and streptomycin. Multilocus sequence types ST32 (61%), ST309 (37%), and ST367 (2%) were strongly linked to the serovars Salmonella Infantis, Salmonella Kiambu, and Salmonella Cerro, respectively. Whole genome sequencing of Salmonella isolates detected only 2 resistance genes: aac(6′) gene that confers resistance against aminoglycosides among 40.7% of the isolates, and a single isolate positive for the blaDHA-16 gene. Two distinct clusters among the serovars were observed suggesting 2 independent sources of spread. Despite the low prevalence of antimicrobial resistance among Salmonella from the dairy farms, our findings contribute to the regional and national understanding of antimicrobial resistance in dairy herds in Australia. There is need for continued antimicrobial resistance stewardship and surveillance programs to ensure the production of high-quality food products and the long-term protection of both animal and human health.